2022
DOI: 10.1038/s41398-022-01941-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomic analysis in plasma and cerebrospinal fluid of humans and in plasma and brain of mice following antidepressant-dose ketamine administration

Abstract: Subanesthetic-dose racemic (R,S)-ketamine (ketamine) produces rapid, robust, and sustained antidepressant effects in major depressive disorder (MDD) and bipolar disorder (BD) and has also been shown to effectively treat neuropathic pain, complex regional pain syndrome, and post-traumatic stress disorder (PTSD). However, to date, its mechanism of action remains unclear. Preclinical studies found that (2 R,6 R;2 S,6 S)-hydroxynorketamine (HNK), a major circulating metabolite of ketamine, elicits antidepressant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…Comparison with a recent report describing principal metabolomic components in the plasma and the CSF in nine "normal" volunteers following a single IV ketamine infusion may provide additional context [ 32 ]. In that study, 87 CSF metabolites were clustered into four components, with only PC2 exhibiting consistent changes over 28 h. Serum and CSF loadings were in opposite directions for leucine, isoleucine, tryptophan, methionine, and tyrosine.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with a recent report describing principal metabolomic components in the plasma and the CSF in nine "normal" volunteers following a single IV ketamine infusion may provide additional context [ 32 ]. In that study, 87 CSF metabolites were clustered into four components, with only PC2 exhibiting consistent changes over 28 h. Serum and CSF loadings were in opposite directions for leucine, isoleucine, tryptophan, methionine, and tyrosine.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, circulating plasma levels of some metabolites did not always mirror CSF levels. For example, branched-chain amino acids increased in the plasma of healthy volunteers post-ketamine but decreased in the CSF, indicating the importance of assaying CSF for metabolic markers of interest in brain conditions [26].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites were extracted in plasma (10 μL) following a previously described protocol (Moaddel et al, 2022). For urine samples (10 μL) were extracted following a similar protocol with slight changes (http://www.biocrates), including an extended calibration range to account for urine metabolite concentrations, an additional creatinine internal standard was added to account for higher creatinine concentrations with an additional drying step, and a solution of 350 mM urea, 15 mM NaHPO4, pH 6.0 was used as zero samples.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this interpretation we observed an increase in Kyn and the immune checkpoint protein, indoleamine 2,3-dioxygenase (IDO) activity (Kyn/Trp ratio). IDO activity is upregulated by pro-inflammatory cytokines (Moaddel et al, 2022), is high in nonagenarians and has been found to be associated with higher mortality and frailty in older persons (Marttila et al, 2011).…”
Section: Differences In the Plasma Metabolome With Agingmentioning
confidence: 99%
See 1 more Smart Citation